Flash rate discrimination in rats: Rate bisection and generalization peak shift - Fox, Andrew T.; Smethells, John R.; Reilly, Mark P. (Journal of the experimental analysis of behavior, 2013)
Two experiments were conducted to determine whether responding by albino rats can be brought under the stimulus control of different flash rates. In the first experiment, a conditional discrimination procedure was employed whereby two different flash rates (fast or slow) signaled the availability of reinforcement on one of two levers (left or right). Stimulus control emerged rapidly and improved with continued training. When intermediate flash rates were presented during probe sessions, the bisection point of the fast and slow flash rates was near their geometric mean, consistent with research employing other stimulus types. In the second experiment, a successive discrimination procedure was employed whereby responding in the presence of one flash rate (S+) was reinforced while responding in the presence of another flash rate (S−) was not reinforced. Again, stimulus control emerged quickly and improved with continued training. Test sessions in which many different flash rates were presented for brief periods in extinction revealed the peak shift phenomenon, in which peak response rates are shifted from the S+ in a direction away from the S−. Flash rate is endorsed as a continuous stimulus dimension that is useful for differentially signaling schedule components.